Study on the influence mechanism of students’ behavior of participation in industrial colleges—Analysis framework based on theory of planned behavior - Zhang, Yuanbao; Shen, Xiangdong; Song, Jinyu; Huang, Tiantian (Frontiers in Psychology, 2022)
As a new organizational form for the coordinated development of education and industry, industrial college is an important carrier for application-oriented colleges and universities to implement application-oriented talent training. Based on Theory of Planned Behavior (TPB) as a theoretical framework, this research constructs a model of the influencing factors of college students’ participating in industrial colleges from five criteria: behavioral attitudes, subjective norms, perceived behavioral control, behavioral intentions and situational factors. In this study, participants (N = 541) have completed a questionnaire to assess their behavior of participation in the industrial colleges by using the structural equation model (SEM). It turns out that perceived needs, mandatory norms, exemplary norms, and self-efficacy significantly positively affect college students’ intention to participate in industrial colleges. Behavior intention and self-efficacy significantly positively affect college students’ participation in industrial colleges. Behavior intentions act as a complete mediator between perceived needs and behavior, as well as between exemplary norms and behavior. Behavioral intentions partially mediate between mandatory norms and behavior, as well as between self-efficacy and behavior. In addition, school support plays a significant positive moderating role in college students’ intention and behavior of participating in industrial colleges. These findings not only expand the relevant literature on college students’ learning behavior, but also provide useful enlightenment for college education managers on how to stimulate college students’ endogenous motivation to participate in industrial colleges.